KONSEP PENDIDIKAN ANAK DALAM KELUARGA MENURUT IBRAHIM AMINI - Malta Malta; Syarnubi Syarnubi; Sukirman Sukirman (PAI RAFAH, 2022)
The family environment is the first and foremost educational environment for children. Thus it can be said that parents are the first and foremost educators in the formation of a child's personality. Ibrahim Amini also believes that education needs to be nurtured from the beginning of a child's development. Because, in fact, children's education is the responsibility of their parents, children's education begins at home, that is, parents are the first teachers for their children.The type of research used in this research is library research. Literature research is research that uses reading materials as a reference source. It means collecting data by reading, studying, understanding and analyzing documents related to the research. Data collection techniques used are documentation and observation. While the data analysis method used is using content analysis.The results of the study state that the concept of children's education in the family is first, children's education starts from choosing a partner. Second, children's education begins during pregnancy. third, children's education in the first year or two. While the relevance of, showing how important the role of parents or families in educating their children is because the first madrasa for children is the second parent, teaching manners and morals. Third, teach morality. Third, obey your parents.